2014
DOI: 10.1371/journal.pone.0096384
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL-40 Level Is Associated with the Chemotherapy Response and Prognosis of Patients with Small Cell Lung Cancer

Abstract: This study was to explore the association between the serum YKL-40 level and the clinical characteristics, the response to chemotherapy and prognosis in small cell lung cancer (SCLC). Serum YKL-40 levels were detected and compared in 120 patients with SCLC pre- and post-chemotherapy, and in 40 healthy controls. Receiver operating characteristics (ROC) curves were adopted for diagnosis and calculation of area under ROC curve in SCLC. The Kaplan–Meier method, univariate and multivariate Cox regression analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…In another study, it was shown that YKL-40 is a potential prognostic marker of chemotherapy response in SCLC. Serum levels of YKL-40 were significantly correlated with disease stage, while there were no difference with age, gender, smoking status and performance status in this study (24).…”
Section: Discussioncontrasting
confidence: 58%
“…In another study, it was shown that YKL-40 is a potential prognostic marker of chemotherapy response in SCLC. Serum levels of YKL-40 were significantly correlated with disease stage, while there were no difference with age, gender, smoking status and performance status in this study (24).…”
Section: Discussioncontrasting
confidence: 58%
“…High CHI3L1 expression was independently associated with poorer overall survival in both NSCLC and SCLC patients (103). Serum CHI3L1 levels in 120 SCLC patients were higher in the group with a poorer response to chemotherapy and those revealing a shorter survival (104).…”
Section: Chi3l1 In Inflammation and Cancermentioning
confidence: 94%
“…Therefore, the 5‐year survival rate of SCLC is still very low . Progastrin‐releasing peptide (ProGRP), YKL‐40 and neuron‐specific enolase (NSE) is commonly used tumor markers for tumor diagnosis . However, these widely used serum marker are not sufficiently accurate to be useful as a diagnostic test.…”
Section: Introductionmentioning
confidence: 99%